Assessing the Iran Scientific Information Database (Ganj) based on User Engagement Scale - hashem Atapour; afshin hamdipour; elaheh shiri (تحقیقات کتابداری و اطلاع‌رسانی دانشگاهی, 2020)
Objective: The main purpose of this study was to evaluate the Iran Scientific Information Database (Ganj) using user engagement scale.Methodology: This research is an applied one. A standard questionnaire for User Engagement Scale was used to collect the data, which is composed of four scales including Focused Attention, Perceived Usability, Aesthetic Appeal, and Reward. SPSS software was used for data analysis. The population of this study is the graduate students of Tabriz University, of which 50 students who declared their readiness to participate in the research was selected as sample.Findings: Results showed that the Focused Attention scale has the lowest and the Perceived Usability scale has the highest average score in both systems. The mean scores for the Attention, Perceived Usability, Aesthetic Appeal, and the Reward were 2.28, 2.77, 2.31, and 2.57 in the previous version of Iran Scientific Information Database (Ganj), and were respectively 2.56, 2.91, 2.79, and 2.84 in the new platform of the same database.Conclusion: Although new platform of ISID (Ganj) is relatively better than its previous version in term of UES, However, in order to improve the user engagement in the new platform, it is necessary to pay more attention to the principles of user interface design.